Key factors in the development of non-governmental women’s associations in modern Russia - E. S. Ryazanova (Вестник Майкопского государственного технологического университета, 2025)
Abstract. The relevance research lies in the expediency of identifying the factors of development of Russian public women’s associations. This will contribute to improving the mechanism of their state support for solving socially significant problems of women, children and families in the country. The problem of the research lies in the comprehensive activation of Russian public associations of women, on the one hand, and in the absence of a conceptual justification of the factors influencing their positive development, on the other hand.The goal of the research is to identify, classify and determine the degree of influence of a complex of different factors on the development of women’s public associations in modern Russia.The research methods. The article uses data from sociological surveys conducted in 2024 in two Russian regions - Belgorod and Moscow regions. First, it is a questionnaire survey of women who are employees or volunteers of Russian public associations of women. Secondly, this is an interview with experts from among managers and scientists.The results. Among the external factors, the most important are the improvement of women’s educational programs and state support for women’s structures, as well as a large amount of daily unpaid work for Russians at home, the effect of conservative gender stereotypes, and the fear of residents of border territories for the life and health of loved ones. Among the internal factors (operating within organizations), cooperation with the authorities, increasing the financial base, professional and personal development, digitalization have been highlighted.Key findings. It is advisable to divide the key factors of the development of women’s public associations in modern Russia into external and internal ones, taking into account their heterogeneity, the varying degree of influence on women’s structures, as well as the difference in opinions of employees and volunteers, on the one hand, and experts, on the other.